2018
DOI: 10.3390/md16120515
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Number of Adipose Lineage and Endothelial Cells in Epididymal fat in Response to Omega-3 PUFA in Mice Fed High-Fat Diet

Abstract: We found previously that white adipose tissue (WAT) hyperplasia in obese mice was limited by dietary omega-3 polyunsaturated fatty acids (omega-3 PUFA). Here we aimed to characterize the underlying mechanism. C57BL/6N mice were fed a high-fat diet supplemented or not with omega-3 PUFA for one week or eight weeks; mice fed a standard chow diet were also used. In epididymal WAT (eWAT), DNA content was quantified, immunohistochemical analysis was used to reveal the size of adipocytes and macrophage content, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 82 publications
2
10
0
Order By: Relevance
“…Our findings are also consistent with several in vitro studies in 3T3-L1 adipocytes showing that n-3 HUFAs reduce TAG accumulation during differentiation [32][33][34]. In addition, these effects have also been reported in mammalian in vivo studies, where high-fat diets containing n-3 HUFAs limited the hypertrophy of fat depots [35][36][37][38][39][40]. The enhanced amount of lipid droplets in the OA-treated adipocytes correlated well with the higher presence of FATP1 at both the protein and transcript level, indicating its involvement in FA uptake and TAG synthesis.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are also consistent with several in vitro studies in 3T3-L1 adipocytes showing that n-3 HUFAs reduce TAG accumulation during differentiation [32][33][34]. In addition, these effects have also been reported in mammalian in vivo studies, where high-fat diets containing n-3 HUFAs limited the hypertrophy of fat depots [35][36][37][38][39][40]. The enhanced amount of lipid droplets in the OA-treated adipocytes correlated well with the higher presence of FATP1 at both the protein and transcript level, indicating its involvement in FA uptake and TAG synthesis.…”
Section: Discussionsupporting
confidence: 92%
“…It is known that ω-3 FA is able to reduce hypertrophy of adipocytes (Kopecky et al, 2009;de Sá et al, 2016) as well as the growth of adipose mass, which many authors justify it by an inhibition of adipocytes proliferation (Adamcova et al, 2018;Hensler et al, 2011;Masoodi, Kuda, Rossmeisl, Flachs, & Kopecky, 2014). Interestingly, we observed that the treatment with ω-3 partially reduced the WAT mass depot (17% in ING and 13% in RP) and when the size of the cells was measured, there was a total reversal of hypertrophy with a concomitant increase in hyperplasia in both depots (119% and 170% of increase in cell number for ING and RP, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the results of microarray analysis, RT-qPCR was performed as described [9]. Data were normalized to the level of villin expression.…”
Section: Real-time Quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…In terms of the effect of dietary fatty acids (FA) on metabolism, supplementation with polyunsaturated FA of n-3 series (Omega-3) such as eicosapentaenoic acid (EPA; 20:5n-3) and docosahexaenoic acid (DHA; 22:6n-3), which are found in marine fish and fish oils, could reduce the risk of cardiovascular disease [2]. Several studies in obese humans also demonstrated a reduction of adiposity after Omega-3 supplementation [3,4], while Omega-3 prevented the development of obesity, insulin resistance, and dyslipidemia in rodents fed a high-fat diet [5][6][7][8][9]. Moreover, Omega-3 may reduce liver steatosis ( [5,10], and reviewed in [11]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation